Islamic Legal Thought as An Integrative System: Ontological, Epistemological, and Axiological Analysis in The Discourse of Ius Integrum Nusantara - Lubis, Ikhsan; Parinduri, Hermawati; Sari Lubis, Duma Indah; Lubis, Andi Hakim (Islam Futura, 2026)
Contemporary Islamic legal studies are often marked by conceptual fragmentation, where law is examined separately as juridical norms, ethical values, or social practices. This condition raises a fundamental question regarding how the integrative character of Islamic legal thought can be adequately understood and articulated. This article positions itself as a normative–philosophical legal study with a qualitative and reflective character, employing conceptual and philosophy of law approaches to analyze Islamic legal thought as an integrative system. The study relies on secondary legal materials collected through library research and analyzed through conceptual-critical and dialogical methods. It proposes an integrative framework based on ontology, epistemology, and axiology. In this framework, Islamic law is examined ontologically as part of a relational and meaningful order of life, epistemologically as a dynamic process of legal knowledge formation involving revelation, reason, and social experience, and axiologically as a value-oriented practice grounded in justice, welfare, and moral responsibility. The discourse of Ius Integrum Nusantara is employed to situate this framework within the Nusantara context, not as a fixed legal theory, but as a dialogical orientation that connects Islamic legal thought with local legal experience, cultural plurality, and social practice. The main result demonstrates that the integration of norms, values, and social practices is not external to Islamic law, but constitutes a structural characteristic of Islamic legal thought itself. Within the discourse of Ius Integrum Nusantara, this integration opens possibilities for more reflective, context-sensitive, and culturally grounded approaches in contemporary Islamic legal studies